THE DESIGN OF ISLAMIC EDUCATION LEARNING USING WORDWALL MEDIA: A CASE STUDI AT SMPIT AT-TAUFIQ - Maulida Fithria; Abdul Ghofur; Ahmad S ofyan (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to examine how Islamic Religious Education (PAI) teachers design PAI learning using Wordwall media to support the learning process at SMPIT At-Taufiq in Depok City. The indicators investigated include the implementation of Wordwall-based instructional design by PAI teachers, as well as the interaction between teachers and students during the PAI learning process using the Wordwall platform. The research method employed is a case study with a qualitative approach. Data collection procedures involved observation, interviews, and documentation. Data validity was tested through triangulation of sources, techniques, and time. Data were analyzed through data reduction, data presentation, and drawing conclusions. The findings reveal that the implementation of PAI learning using Wordwall media consists of three stages: pre-learning, the learning process, and post-learning. PAI learning with Wordwall aligns with Vygotsky's constructivist learning theory, providing a comprehensive approach through digital learning in a game-based environment. Students appeared more focused in understanding the material, enthusiastic, and actively collaborated during group discussions.